Neurorehabilitation for Multiple Sclerosis Patients with Emotional Dysfunctions - Hung, Yuwen; Yarmak, Pavel (Frontiers in Neurology, 2016)
Depression frequently develops in multiple sclerosis (MS) patients, exacerbating the manifestations of the disease and making its management challenging. To date, no consensus has been reached regarding effective treatments for these sufferers due to limited understanding regarding the underlying mechanisms responsible for emotional disorders that are highly comorbid with this disease. There is an urgent need to rethink current treatment options for these patients. This article aims to optimize the treatment outcomes and improve the quality of life for MS patients. Based on an in-depth and critical review of the current literature, we provide a neurorehabilitative framework that explains possible regulatory mechanisms underlying the emotional symptoms highly developed in MS. This article offers practical knowledge and therapeutic strategies to optimize the treatment options in the current care system for MS, as well as for other disabling diseases.